Math you can't use : patents, copyright, and software - Klemens, Ben (Brookings Institution Press, 2006)
"Gathering persepectives from law, computer science, mathematics, and economics, examines the intellectual property issues surrounding computer software and suggests how patents might accommodate the unique structure of code and copyright for software could be more effectively implemented"--Provided by publisher
Keywords: Intellectual property.; Intellectual property -- United States.; Computer software -- Law and legislation.; Intellectual Property; Propriété intellectuelle.; Propriété intellectuelle -- États-Unis.; intellectual property.; LAW -- Business & Financial.; LAW -- Intellectual Property -- General.; COMPUTERS -- Programming -- General.; Computer software -- Law and legislation; Intellectual property; United States; Geistiges Eigentum; Programm; Softwaremarkt; Urheberrecht; USA; droit d'auteur -- informatique -- propriété intellectuelle et industrielle -- Etats-Unis.